Pengaruh Debt Financing Dan Equity Financing Terhadap Kinerja Keuangan Bank Syariah Dengan Non Performing Financing Sebagai Variable Moderating - Andi Rasti Utari Dwi Rahayu; Saiful Muchlis; Hasbiuallah Hasbiuallah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2018)
This study aims to analyze the financial performance of sharia commercial banks in particular related to the channeling of funds in this case debt financing and equity financingand non performing financing as a moderating variable of the two previous variables to determine the financial performance of sharia commercial banks. The subject of this researchis sharia commercial bank listing in Bank Indonesia year 2011-2015. This research is associative, sample selection is done by purposive sampling method, sothat 8 syariah banks that fulfill the criteria of 11 sharia commercial banks listing in BI Thedata used in the form of secondary data derived from financial statements and annual reports,while data analysis techniques used are descriptive statistical analysis and multipleregression analysis and for analysis of moderating variable using test of absolute differencevalue. The results of this study indicate that debt financing and equity financing have asignificant and positive impact on the financial performance of sharia banks. And nonperforming financing is only able to moderate equity financing to the financial performanceof sharia banks. While non performing financing can not moderate the relationship betweendebt financing to the financial performance of sharia banks